World meetings.
Medical meetings to be held all over the world. Main entry section (arranged in accession order) gives meeting details, i.e., name, location, hotel, sponsor, contact person for general information, contents, expected attendance, paper deadlines, publication information, and contact person for exhibits. Keyword, date, location, and sponsor indexes.